Profiling the segments of visitors in recreational forests / Nitanan Koshy Matthew, Chin Kee Tom and Velan Kunjuraman - Matthew, Nitanan Koshy; Chin, Kee Tom; Kunjuraman, Velan (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The identification and understanding of the needs of the customers are important. Failure to do such would fail to address the needs of visitors. On the same note, there is a lack of data on visitors' profiles and perceptions on the facilities and services given in the forest. Hence, this study has focused on the distinction between the socio-demographic, characteristics of the visit, and customers' satisfaction of the recreation and facilities of a popular recreational site, namely, the Melaka Botanical Garden in Melaka. On-site data were collected from a sample of the visitors. The satisfaction levels of the visitors were evaluated using the perception analysis. The study found that the majority of the respondents in the MBG were male adults between 25 to 54 years old, had completed at least diploma level education, single, came from the Melaka state, students, recreational activities as purpose of visit, almost three quarters of the respondents were willing to donate for the annual donation for conservation and management of the recreational forest, and the visitors had a medium level of satisfaction with the facilities. The outcome is expected to be a guide for the operators of recreational forests to arrange and improve any recreational site.